Exploration of the Repentance Aspect of Pwahaci Dance in Seren Taun Ritual in Cigugur, West Java - Swaradesy, Rufus Goang; Subiantoro, Ignasius Herry; Sundari, Nanda (Institut Seni Indonesia Denpasar, 2026)
Repentance shows man's awareness of his weakness before God. As weak creatures, humans should communicate with God to be grateful for the goodness given and also ask God for help. The provision of help from God to humans is depicted as beautiful, like a mother's love for her child. This research uses a qualitative approach with the main focus on the meaning of the Pwahaci dance repentance in the seren taun ritual in the Cigugur Kuningan community in West Java. Data collection was done by observation, interview, and literature study. The data obtained was then reduced to make it more focused, and an in-depth analysis was carried out using Hans Urs Von Balthasar's religious aesthetic perspective. The results of the data analysis are then presented in the form of scientific writing. The result of this research is that the figure of Dewi Pwahaci is understood as an intermediary between humans and God. Communication is done through a sacred dance, the Pwahaci Dance. This is manifested in the form of meditative Pwahaci dance movements full of truth, goodness, and beauty.